The Core for Economies with Asymmetric Information: An Axiomatic Approach - Darin Lee; Oscar Volij (Brown University, Department of Economics, 1997)
We propose two generalizations of the Davis and Maschler (1965) reduced game property to economies with asymmetric information and apply them in the characterization of two solution concepts. One is Wilson's (1978) Coarse Core and the other is a subsolution of it which we call the Coarse+ Core.
Keywords: 330